Numerical analysis of fatigue crack growth under SuperBlock2020 load sequence. (1st February 2022) - Neto, D.M.; Borges, M.F.; Antunes, F.V.; Sunder, R.
Highlights: SuperBlock2020 is composed of pairs of load blocks, separated by overloads. The load blocks started from the minimum or maximum loads of the overload. The load patterns produced different residual stresses ahead of crack tip. A numerical approach was used to predict FCG rate based on cumulative plastic strain. The numerical predictions are according the experimental trends. Crack closure was found to be the main mechanism behind crack growth trends. Abstract: The components are usually submitted to variable amplitude loading, and it is important to understand the mechanisms explaining fatigue crack growth (FCG) rate variations. The relative importance of residual stresses and crack closure, in particular, is a controversial issue. This work studies a specific load pattern, called Super Block 2020, composed of four pairs of load blocks of different amplitude (A, B, C and D) and the same maximum load, separated by overloads. The transition from the overloads to the constant amplitude load blocks occurred alternatively from the maximum or minimum loads of the overload cycles. These patterns, called i1 and i2 for load blocks i (i = A, B, C or D), produce different residual stresses ahead of crack tip. A numerical procedure was followed to predict FCG rate in the 2024-T351 aluminium alloy, based on cumulative plastic strain. This approach includes the effects of material hardening, crack tip blunting, crack closure and partial crack closure. A significant difference was found between FCG rate and crack increments produced by i1 and i2 load blocks. The numerical predictions are according the experimental trends and crack closure was found to be the main mechanism behind FCG trends.